Politics in Swaziland, 1960 to 1968: A selection of reports in the Times of Swaziland - Ndwandwe, Sishayi Simon (My University, 1968)
This collection of newspaper reports constitutes a personal record of what was said between 1960 and 1968 through the forum of the Times of Swaziland, the only newspaper in the country. (Izwi lama Swazi folded up long ago). Editorials have been omitted, chiefly for reasons of copyright, and the selections made are concerned with the actions of political groups rather than the opinions of individuals.
African Studies Seminar series. Paper presented 1968.
Keywords: Political parties. Swaziland; Swaziland. Politics and government, To 1968